ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP PENDAPATAN PERUSAHAAN PRODUSEN KARET KONSTRUKSI - Fazila, Anisa Ken; Kamilah, Nisrina; Exantiago, Gilang Ramadan; Nugraheni, Atiqah; Ratnaningsih, Rini (Value : Journal of Management and Business, 2024)
In the context of a company, Accounting Information Systems (AIS) play a crucial role in supporting operations and decision-making. Effective internal controls are also essential to ensure the reliability and security of the company's information systems. Continuous eval_uation of information systems and internal controls is necessary to adapt to changes in the business environment and the company's needs, thus optimizing AIS to support its business objectives. This report aims to provide a deep understanding of the revenue cycle management policy at Construction Rubber Manufacturer Company, including related functions, records, and documents used in the company's revenue cycle. Another goal is to eval_uate the adequacy of internal controls applied at Construction Rubber Manufacturer Company explain the data flow in the Data Flow Diagram for the company's revenue cycle. It is expected that this report will provide a comprehensive overview of revenue cycle management at Construction Rubber Manufacturer Company. In this study, the author used two main methods to collect data: interviews and documentation. These methods were chosen because they can provide comprehensive and in-depth information about Construction Rubber Manufacturer Company 's revenue cycle. An analysis of Construction Rubber Manufacturer Company 's revenue cycle shows that the process begins with product offers from the sales team, followed by handling order specifications by the sales team and transaction recording by the accounting department using Accurate software. Construction Rubber Manufacturer Company uses an accounting information system for the revenue cycle with eight related functions and various documents such as price quotation letters, testing certificates, and tax invoices. The company also implements controls to minimize risks, and the context diagram shows processes involving entities such as marketing, production, shipping, and administration.